Physical Exercise and Its Effects on Alzheimer's Disease - Stein, A. M. [UNESP]; Pedroso, R. V. [UNESP] (Elsevier, 2017)
Physical exercise has frequently been the target of research studies related to the treatment of Alzheimer's disease. The level and routine of physical exercise can influence the progression of the disease, as well as influence the intensity of the deleterious effects from Alzheimer's disease. The objective of this article is to introduce the reader to this subject and point out the main findings in scientific literature related to physical exercise and its effects on Alzheimer's disease. This article will identify the general characteristics of the disease, the exercise programs currently used, and the main effects for each of these topics. It will also address a very current topic related to this issue, blood markers, and other techniques for future studies with this population.
Keywords: Adapted physical education; Alzheimer's disease; Health; Level of physical activity; Physical exercise